1983
DOI: 10.1083/jcb.97.4.974
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the 110-kdalton actin-calmodulin-, and membrane-binding protein from microvilli of intestinal epithelial cells.

Abstract: One of the major proteins of the chicken intestinal microvillus is a calmodulinbinding protein of 105-110 kdaltons which has been tentatively identified as the bridge linking the microvillar filament bundle laterally to the membrane. We have treated isolated, membrane-intact brush borders with ATP and obtained solubilization of the 110-kdalton protein, calmodulin (CM), myosin, and lesser amounts of several other cytoskeletal proteins. Electron micrographs of ATP-extracted brush borders showed loss of the linke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
92
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(97 citation statements)
references
References 48 publications
(74 reference statements)
5
92
0
Order By: Relevance
“…Bundling of the 20 or so actin filaments that are found in each intestinal microvillus probably occurs with the aid of villin, an actin-binding protein, and fimbrin (Matsudaira et al, 1983). The folding of the lipid membrane occurs by cross-linking of the actin filaments to a membrane protein(s) via the 110 kDa protein-calmodulin complex (Howe & Mooseker, 1983). A 140kDa protein, recently purified and characterized , is implicated as the membrane protein participating in this folding/microvillar-elongation process.…”
Section: Formation Of the Mnicrovillusmentioning
confidence: 99%
“…Bundling of the 20 or so actin filaments that are found in each intestinal microvillus probably occurs with the aid of villin, an actin-binding protein, and fimbrin (Matsudaira et al, 1983). The folding of the lipid membrane occurs by cross-linking of the actin filaments to a membrane protein(s) via the 110 kDa protein-calmodulin complex (Howe & Mooseker, 1983). A 140kDa protein, recently purified and characterized , is implicated as the membrane protein participating in this folding/microvillar-elongation process.…”
Section: Formation Of the Mnicrovillusmentioning
confidence: 99%
“…The ll0-kD protein is a main component of the lateral bridges that connect the core bundle to the surrounding plasma membrane (13,31,37,46,47,69). Two recent studies indicate that the 110-kD protein shares several properties of a myosin-like mechanoenzyme (12,14).…”
Section: Llo-kd Protein and Tubulinmentioning
confidence: 99%
“…With respect to the ll0-kD protein, there is increasing evidence that it shares several properties of a myosin-related mechanoprotein (12,14). This has led to the suggestion that the ll0-kD protein may not only link the core bundle to the plasma membrane (13,31,37,46,47) but may also connect vesicles to the rootlet bundles and thus may play a role in transport of vesicles through the terminal web (14).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the GPIIb-III membrane actin complex bound with high efficiency to rabbit f-actin in vitro in a Ca++-independent manner, whereas the monomeric forms found in the Triton-soluble fraction did not bind to actin. These results indicate that two forms of GPllb and III exist: one that binds directly to endogenous membrane actin and one that does not.Numerous studies have provided largely indirect evidence for transmembrane interactions among surface proteins and receptors of cells and an internal membrane matrix composed of actin and other cytoskeletal proteins (3,5,7,10,14,16,17,19,23,25,27,31,35,40,45). Indeed, a number of studies have shown that the surface topography and lateral mobility of receptors can be modulated by the underlying cytoskeleton and its associated contractile and motile elements (20,28,30,31,36,37,39).…”
mentioning
confidence: 99%